Uwagi do heterotopii szkoły i jej utopijnej intencji - Barański, Jarosław (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2016)
According to Kurd Lasswitz, the founder of German science fiction, technological utopias of educational system provoke the fundamental question of the functions and objectives of a school, question of tension between its utopian intention and heterotopian space that it occupies. The article is an attempt to define the extent of heterotopian school space and its product – tops of the class, presenting school as cultural tool of civilizing process.
Keywords: Lasswitz; utopia; heterotopia; education; school